Positive effects of biocholine powder dietary supplementation on milk production and quality, and antioxidant responses in lactating ewes: A new nutritional tool - Alba D.F.* (2021)
© 2021We determined whether the dietary supplementation with a commercial product (vegetable biocholine - VB) for Lacaune ewes at peak lactation would improve animal health and production as well as milk quality. We also determined the effects of VB as a feed additive. We used thirty Lacaune ewes at 30 days of lactation, allocated into three groups: T0 (control, without VB), T5 (5 g of VB/animal/day) and T10 (10 g of VB/animal/day). T10 sheep had greater milk yield during the experimental period. T10 ewes had also a significantly lower feed conversion ratio than the other groups. Total solids concentration of milk was higher in T10 than in the other groups on day 20. The somatic cell count in milk was lower in ewes that consumed VB in the highest dose (T10) than in the T0 and T5 in days 15 and 20. Lower levels of lipoperoxidation (LPO) and of reactive oxygen species (ROS) were observed in milk from ewes fed with the VB supplemented diet on day 20, associated with increased levels of total antioxidant capacity and superoxide dismutase activity in milk. In serum, we found that T5 and T10 animals had significantly higher levels of non-enzymatic antioxidants (non-protein thiols) associated with reduced LPO and ROS content. Higher levels of globulins were observed in T10 than in T0 sheep on day 20. These data suggest that VB dietary supplementation stimulates antioxidant responses and increases the concentration of globulins in a manner beneficial to sheep health. Milk production, feed conversion rate, and milk SCC were also improved.